Identification of white rot fungus CP9 and its potential application in biopulping - Lien, Nguyen Thi Hong; Hieu, Nguyen Van; Hong, Luong Thi; Anh, Hy Tuan; Thao, Phan Thi Hong (Vietnam Journal of Biotechnology, 2018)
Wood-rotting fungi represent an important component of forest ecosystems. Among them, white-rot fungi are the most efficient lignin degraders. Biopulping using white-rot fungi in pretreatment of the materials, is one of the solutions to overcome disadvantages of traditional production methods. Today, the isolation and screening of lignin degrading fungi capable for application in biopulping are of keen interest in Vietnam. The use of non–wood, plant fibres in pulp and paper industry, special, agricultural residuces such as rice and wheat straw, sugarcane baggase, cornstalks etc is the new production toward, potential, serving sustainable development. The fungus CP9, which possessed high ligninolytic activity, was identified and studied in pretreatment of rice straw for biopulping. The fruiting bodies of strain CP9 were effuse on trunk. The hymenium was porous and brown white with short tubes, the white mycelia penetrated wood block. The colony was off-white, blossom, irregularly circular. The mycelia were thick and closely bound together. Beside lignin, this fungus could degrade other substrates such as casein, carboxymethyl cellulose and starch. Biological and morphological characteristics of the fungus CP9 suggested its placement in subdivision Basidiomycota. Combined with the results of phylogenetic analysis, which showed 99% similarity of the fungus with species Leiotrametes lactinea, our strain was named as Leiotrametes lactinea CP9. This fungus could grow well on rice straw under solid state fermentation. Pretreatment of rice straw using L. lactinea CP9 was based on the activity of fungal lignin peroxidase and laccase. After 20 days, the residual enzyme activity was of 21.6 and 18.4 nkat/g material for lignin peroxidase and laccase, respectively. Pretreatment significantly improved the quality of straw, as lignin loss of 38% while cellulosic fibers were comparatively well preserved